2018
DOI: 10.3389/fmicb.2018.00945
|View full text |Cite
|
Sign up to set email alerts
|

Lactation Stage-Dependency of the Sow Milk Microbiota

Abstract: Breast milk is essential for the initial development of neonatal animals, as it provides not only essential nutrients and a broad range of bioactive compounds but also commensal bacteria. The milk microbiota contributes to the “initial” intestinal microbiota of infants and also plays a crucial role in modulating and influencing neonatal health. However, the milk microbiota of sows has yet to be systematically investigated. The goal of the present study was to characterize variations in bacterial diversity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(76 citation statements)
references
References 59 publications
8
68
0
Order By: Relevance
“…Nutrient content in milk likely favors colonization and/or proliferation of certain bacteria. We found similar patterns in certain bacterial genera changing with nutrient content as in suid milk (Chen et al, ); Prevotella and Lactobacillus spp. were positively correlated with fat content, but negatively correlated with protein content.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Nutrient content in milk likely favors colonization and/or proliferation of certain bacteria. We found similar patterns in certain bacterial genera changing with nutrient content as in suid milk (Chen et al, ); Prevotella and Lactobacillus spp. were positively correlated with fat content, but negatively correlated with protein content.…”
Section: Discussionsupporting
confidence: 79%
“…Other studies have examined change over lactation in microbiome composition, but with either fewer sampling time points or in a more narrow window of time (Cabrera‐Rubio et al, ; Chen et al, ; Hunt et al, ; McInnis et al, ). Those studies as a whole have revealed the microbiome change is reasonably complex (Cabrera‐Rubio et al, ; Hunt et al, ), with the most predictable and pronounced changes occurring during the transition from colostrum to mature milk (Chen et al, ), and the weaning lactation (McInnis et al, ). We sampled western lowland gorillas and Sumatran orangutans during the mature milk stage and found a bacterial community that changed in the number of bacterial taxa and composition over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gradual maturation of gut immune function and the microbiota may contribute to the decrease in Proteobacteria. Recently, studies have shown that Proteobacteria is one of the most dominant phyla in human (Moossavi et al, 2019) and porcine milk (Chen et al, 2018). Although the origin of the bacteria in breast milk is currently not known, bacteria in breast milk may be an important source of the intestinal microbiota of infants and sucking piglets.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been well established that the gut microbiota composition is inconsistent in mammals during pregnancy [ 4 , 6 ]. For example, the gut microbiota changes dramatically from the first to the third trimesters of pregnancy (e.g., the increased Actinobacteria and Proteobacteria relative abundances and beta diversity and reduced individual richness) [ 4 ]; the intestinal microbiota composition is also dynamic in lactating mammals [ 7 ]. However, the intestinal microbiota variation or difference in the composition during pregnancy and lactation remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%